PENGARUH EFEK MEDIASI PEMBERDAYAAN PSIKOLOGIS TERHADAP GAYA KEPEMIMPINAN DAN KINERJA PADA KARYAWAN BANK BUMN - Andrew Susanto; Kurniawati Kurniawati; Meisya Putri Utami; Carissa Aprilia Zahrah; Delonix Agung (Center for Economic Studies Universitas Katolik Parahyangan, 2022)
Psychological empowerment is one of the empowerment mechanisms that can influence employee attitudes at the individual and team levels. Employee empowerment also helps employees to increase participation more effectively and make things run well in accordance with company goals. Psychologically empowered employees will perceive work as important which can lead to higher job satisfaction. The leadership style that refers to psychological empowerment tends to create high creativity with a sense of commitment that continues to motivate employees to develop skills and knowledge for their performance. The purpose of this study was to improve in testing the role of psychological empowerment on leadership style and task performance of BUMN banks employees. This study uses primary data in the form of filling out questionnaires by 188 employees of BUMN banks as respondents. Collecting of samples using purposive sampling technique because it is based on certain criteria. The data processing method uses the SEM software program.